Evaluation of Tourism Recovery Innovations in D.I. Yogyakarta based on Data Analytics - Ardhitama Shaumarli; Radiani Nurwitasari (ASEAN Journal on Hospitality and Tourism, 2023)
Sector tourism is one of the sectors hardest hit by the Covid-19 pandemic. To accelerate recovery tourism, D.I. Yogyakarta stakeholder collaboration a series of innovations. From the supply side, D.I. Yogyakarta is trying to improve attractions and amenities, following the shifting in preferences of tourists. For increasing demand side, collaboration to intensified promotion healthy tourism. This study trying to measure how effective the innovation efforts to tourism recovery and identifying factors that affect them. Furthermore, efforts necessary to conduct could accelerate the satisfaction level of tourists and increase D.I. Yogyakarta tourism branding power, leading to an increase in the quantity and quality of visit travelers to the D.I. Yogyakarta territory. This study has a combined approach, both qualitative and quantitative. Primary data was obtained from Focus Group Discussions with tourism stakeholders. Secondary data mainly used is the unstructured data obtained from TripAdvisor, Twitter, and Instagram. Analysis tools are used based on sentiment analysis, deep learning, and social network analysis. Generally, the innovations made by D.I. Yogyakarta have an positive impact to the satisfaction traveler and strengthen the D.I. Yogyakarta tourism brand. Even in 2021, when the Covid case reach the peak, the rating even reach the highest rating value. Increasing of the satisfaction, as an impact from the improvement of service, comfort, and cleanliness objects and amenities. Meanwhile strengthening brand and image of D.I. Yogyakarta tourism also tends to increase except for some conditions.